Cost-Effective 40-Gbaud THP PS-PAM-4 C-Band IM/DD Transmission for 50-km Inter-DCI Utilizing 2-bit DAC - Zhuo Chen; Zipeng Liang; Junyu Wu; Weiqi Lu; Xinyu Chang; Xiaoxiao Dai; Qi Yang; Chen Liu; Mengfan Cheng; Lei Deng; Deming Liu; William Shieh (IEEE Photonics Journal, 2024)
Data center interconnections are cost-sensitive. We propose and demonstrate a cost-effective C-band intensity modulation direct detection (IM/DD) transmitter for extended range (ER) inter-datacenter interconnects utilizing only a 2-bit digital-to-analog converter (DAC). Tomlinson-Harashima precoding (THP) is used in transmitter DSP to compensate for dispersion-induced impairments. Due to the uniform distribution of signal levels after THP encoding, a high-resolution DAC is required to generate electrical signals. The hardware cost of the transmitter can be significantly reduced by compressing the physical number of bits (PNOB) of the DAC to 2 bits. We quantize the signal to 4 levels and utilize up-sampling and noise shaping to greatly reduce the in-band quantization noise. The in-band signal to noise ratio (SNR) can be increased to 23 dB. We experimentally demonstrate a cost-effective 40-Gbaud probabilistic shaping PAM-4 C-band IM/DD transmission over 50-km utilizing only a 2-bit DAC in the transmitter without any optical dispersion compensation. The performance of the proposed scheme is proximate to the common case of using an 8-bit DAC. It has a BER gap of about 2 × 10−3 only when the received optical power (ROP) is higher than −6 dBm.